Glow discharge electrolysis plasma initiated synthesis of upconversion luminescent and temperature sensitive multifunctional hydrogel. Issue 3 (3rd July 2018) - Zhang, Wenming; Miao, Wenfang; Yue, Ziwei; Liu, Sichen; Li, Ling; Zhang, Zisheng; Wang, Hong
ABSTRACT: In the present work, a novel multifunctional hydrogel that simultaneously possesses strong upconversion luminescence (UL) and temperature responsibility was fabricated based on the crosslinking of hemicellulose and ricinoleic acid capped NaYF4 :Yb/Er in the presence of Poly (N-isopropylacrylamide) (PNIPAM) and polyacrylamide (PAAm) aqueous solution by using glow discharge electrolysis plasma (GDEP) initiated technique. Its structure and properties were characterized by wide angle X-ray diffraction, FT-IR spectra, scanning electron microscopy, transmission electron microscope and fluorescence spectra. The obtained hydrogel exhibited reversibly temperature-dependent UL and highly enhanced sensibility. The luminescence intensity and transmittance of hydrogel showed a sharp decrease in the range of 32–35°C. Furthermore, the luminescence intensity of hydrogel was almost not weakened after five heating-cooling cycles, which may allow their use in remote control thermosensitive switch.